Prevalence and risk factors associated with Leishmania infection in Trang Province, southern Thailand. - Jipada Manomat; Saovanee Leelayoova; Lertwut Bualert; Peerapan Tan-Ariya; Suradej Siripattanapipong; Mathirut Mungthin; Tawee Naaglor; Phunlerd Piyaraj (Public Library of Science (PLoS), 2017)
Autochthonous cutaneous and visceral leishmaniasis (VL) caused by Leishmania martiniquensis and Leishmania siamensis have been considered emerging infectious diseases in Thailand. The disease burden is significantly underestimated, especially the prevalence of Leishmania infection among HIV-positive patients.A cross-sectional study was conducted to determine the prevalence and risk factors associated with Leishmania infection among patients with HIV/AIDS living in Trang province, southern Thailand, between 2015 and 2016. Antibodies against Leishmania infection were assayed using the direct agglutination test (DAT). DNA of Leishmania was detected by ITS1-PCR using the buffy coat. Species of Leishmania were also identified.Of 724 participants, the prevalence of Leishmania infection was 25.1% (182/724) using either DAT or PCR assays. Seroprevalence of Leishmania infection was 18.5% (134/724), while Leishmania DNA detected by the PCR method was 8.4% (61/724). Of these, 24.9% (180/724) were asymptomatic, whereas 0.3% (2/724) were symptomatic VL and VL/CL (cutaneous leishmaniasis). At least five species were identified: L. siamensis, L. martiniquensis, L. donovani complex, L. lainsoni, and L. major. Multivariate analysis showed that CD4+ levels <500 cells/μL and living in stilt houses were independently associated with Leishmania infection. Those who were PCR positive for Leishmania DNA were significantly associated with a detectable viral load, whereas non-injection drug use (NIDU) and CD4+ levels <500 cells/μL were potential risk factors of Leishmania seropositivity.A magnitude of the prevalence of underreporting Leishmania infection among Thai patients with HIV was revealed in this study. Effective public health policy to prevent and control disease transmission is urgently needed.